Socialization of Effective Marketing Strategies to Increase Sales of MSME Products at Khadijah Orphanage, South Jakarta - Fatimah; Nataly, Febryansyah; Purnamasari, Yuli; Zebua, Dedy; El Hida, Ramdania; Setyadji, Veronika; Asfahani, Shulhuly; Mustopa; Wiratama, Adi; Yulistyarani, Tri (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study aims to address the marketing challenges faced by small and medium enterprises (SMEs) at the Khadijah Orphanage, South Jakarta, focusing on improving product appeal, pricing, and promotion to boost sales and income for the orphanage.Method: The research is based on a socialization event held on February 25, 2023, by Universitas Indonesia Maju’s Faculty of Communication Science. Data were gathered through observations and discussions with 25 participants, including orphanage staff and residents.Practical Applications: The findings suggest that SMEs at the orphanage can improve sales by enhancing product appeal, adopting competitive pricing, and expanding promotional efforts through agents, rather than relying solely on direct sales to consumers.Conclusion: Effective marketing strategies, including better product presentation, pricing, and broader promotion channels, can increase the competitiveness of SMEs at the orphanage, contributing to their financial sustainability.